Influence of Green Practices on Organizational Competitiveness: A Study of the Electrical and Electronics Industry. Issue 2 (3rd April 2019) - Sellitto, Miguel Afonso; Hermann, Felipe Fehlberg
Abstract: The purpose of this article is to verify the efficacy of green practices in influencing competitive enablers of organizations in the electrical and electronics industry. This study applies quantitative modeling, supported by a survey of 70 companies in southern Brazil and a structural equations model. The model includes four constructs: green strategy, green innovation, externalities management in green operations, and information management in green operations. The model also includes three factors influenced by the constructs that facilitate the construction of the organizational competitiveness: compliance, strategic drivers, and corporate image. The main result obtained suggests that green strategy and green innovation are more likely to influence competitiveness in the industry, and information management only partially influences competitiveness, while externalities management appears to have no influence.